Method for producing microfiber cellulose, method for producing microfiber cellulose composite resin, and microfiber cellulose

JP7638751B2Active Publication Date: 2025-03-04DAIO PAPER CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021054991
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-04
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0026】 本発明によると、変性処理の変性率が向上されたマイクロ繊維セルロース、マイクロ繊維セルロースの製造方法、及びマイクロ繊維セルロース複合樹脂の製造方法となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638751000003
    Figure 0007638751000003
  • Figure 0007638751000001
    Figure 0007638751000001
  • Figure 0007638751000002
    Figure 0007638751000002
Patent Text Reader

Abstract

To provide a manufacturing method of a micro-fiber cellulose with an improved modification rate in modification treatment, and a manufacturing method of a micro-fiber cellulose composite resin, and a micro-fiber cellulose.SOLUTION: The problem is solved by: a manufacturing method of a micro-fiber cellulose that involves a modification step for modification of a cellulose raw material to obtain a cellulose carbamate and a splitting step of splitting the cellulose carbamate to obtain a micro-fiber cellulose, wherein the modification step is run by adding urea or a derivative thereof and a bipolar ionic compound to the cellulose raw material, followed by heating at 100-300°C; and a manufacturing method of a cellulose composite resin that involves a kneading step of kneading the obtained micro-fiber cellulose and a resin to obtain a cellulose composite resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing microfibrous cellulose, a method for producing a microfibrous cellulose composite resin, and microfibrous cellulose. [Background technology]

[0002] In recent years, fine fibers such as cellulose nanofibers obtained by defibrating raw pulp and microfiber cellulose (microfibrillated cellulose) have attracted attention for use as reinforcing materials for resins, and research and development into these materials is underway. Although fine fibers are useful as reinforcing materials, they are hydrophilic and repel hydrophobic resins, which raises the issue that their effectiveness as a reinforcing material for resins may not be fully realized. To address this issue, a technology has been proposed in which fine fibers are modified by, for example, adding hydrophobic groups to give them the same hydrophobic properties as resins, thereby increasing their affinity with resins and providing a reinforcing effect.

[0003] Patent Document 1 discloses a technique for imparting hydrophobic groups to fine fibers, which involves "a modified cellulose raw material (A) esterified by adding a cyclic polybasic acid anhydride (a) having 15 or more carbon atoms and a hydrophobic group to a cellulose raw material," and proposes that a modified cellulose raw material-containing resin composition that contains this modified cellulose raw material (A) and a dispersing resin (B) will have excellent dispersibility and mechanical strength in resins used as molding materials.

[0004] Patent Document 2 proposes a technology for "a method for producing modified cellulose nanofibers, which comprises the steps of obtaining modified cellulose by reacting cellulose having hydroxyl groups with a resin having a polybasic anhydride structure within the molecule and micronizing the obtained modified cellulose in the same process, wherein the polybasic anhydride structure is a cyclic polybasic anhydride structure in which carboxyl groups are dehydrated and condensed within the molecule to form a cyclic structure," and claims that this technology makes it possible to easily produce modified cellulose nanofibers that are easily dispersible in solvents. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-216605 A [Patent Document 2] WO2015 / 040884 issue Summary of the Invention [Problem to be solved by the invention]

[0006] Patent Document 1 states that it is desirable for the modification rate (reaction rate) of the acid anhydride to the cellulose raw material to be within a predetermined range, but does not give sufficient consideration to what production method can be adopted to improve the modification rate. Patent Document 2 states that cellulose is reacted with a resin having an anhydrous polybasic acid structure in the molecule at a predetermined ratio to produce modified cellulose nanofibers, but again, there is no sufficient consideration given to improving the modification rate. In light of these points, the present inventor believes that there is room for further improvement in the modification rate, and the problem to be solved by the present invention is to provide a microfiber cellulose, a method for producing microfiber cellulose, and a method for producing a microfiber cellulose composite resin, in which the modification rate of the modification treatment is improved. [Means for solving the problem]

[0007] One example of a method for denaturing cellulose is to mix cellulose with urea and heat it. In this case, the degree of contact between the cellulose and urea and the heating temperature determine the denaturation rate. Increasing the heating temperature gives the urea activation energy, which activates the chemical reaction with cellulose and improves the denaturation rate. However, there is a risk that the cellulose may be partially damaged by heat. Cellulose that is heavily damaged has low strength and may be unsuitable as a reinforcing material for resins. Taking this into consideration, the following aspects of the invention have been completed.

[0008] [First aspect] a modification step of modifying a cellulose raw material to obtain carbamate cellulose; A defibration step of defibrating the carbamate cellulose to obtain microfibrous cellulose, The modification step is carried out by adding urea or a derivative thereof and a zwitterionic compound to a cellulose raw material and heating the mixture to 100 to 300°C. A method for producing microfibrous cellulose.

[0009] In the modification process, when urea or its derivatives and a zwitterionic compound are added and heated, they behave like a deep eutectic solvent. In this state, urea or its derivatives are highly reactive and easily react with the cellulose raw material. Therefore, carbamate cellulose with a relatively high modification rate can be obtained without excessive heating of the reaction system.

[0010] [Second aspect] The cellulose raw material is a sheet-like pulp. A method for producing the microfibrous cellulose of the first embodiment.

[0011] The form of the cellulose raw material can be a slurry, a sheet, a fiber, a crushed pulp, or any other pulp form. Among them, when a sheet-like pulp is used as the cellulose raw material, a carbamate cellulose with a high modification rate can be obtained in a relatively short reaction time. The mechanism by which carbamate conversion proceeds in a short time is not clear, but it is presumed that thermal conductivity is one of the factors. If heat is applied to a liquid containing pulp of a certain concentration, in a slurry or fiber-like pulp, the size of each pulp is small, so that the heat is conducted between the pulps through the liquid. If the liquid has poor thermal conductivity, it will take a certain amount of time for the heat to be transmitted to all the pulp in the liquid. On the other hand, in a sheet-like pulp, the size of each pulp is large, so that the heat is directly transmitted within the sheet, regardless of the thermal conductivity of the liquid, and the entire sheet is thought to reach a temperature at which the chemical reaction is promoted in a short time. In addition, if the time of exposure to the temperature at which the carbamate reaction is accelerated is short, damage to the cellulose is small, so that microfibrous cellulose having a relatively high degree of crystallinity can be obtained.

[0012] [Third aspect] The zwitterionic compound is a betaine. A method for producing the microfibrous cellulose according to the first or second aspect.

[0013] If the zwitterionic compound is a betaine, it can be easily mixed with urea or its derivatives to form a deep eutectic solvent, accelerating the carbamate reaction.

[0014] [Fourth aspect] The zwitterionic compound is trimethylglycine or a derivative thereof; A method for producing the microfibrous cellulose according to any one of the first to third aspects.

[0015] If the zwitterionic compound is trimethylglycine or a derivative thereof, it can be easily mixed with urea or a derivative thereof to form a deep eutectic solvent, which promotes the carbamate reaction.

[0016] [Fifth aspect] adding urea or a derivative thereof and a zwitterionic compound in a mass ratio of 1:99 to 99:1; A method for producing the microfibrous cellulose according to any one of the first to fourth aspects.

[0017] When added in this mass ratio, the melting point of the liquid produced by the urea or a derivative thereof and the zwitterionic compound is lowered, facilitating the generation of isocyanic acid, thereby accelerating the carbamate reaction of cellulose.

[0018] [Sixth aspect] The microfiber cellulose has an average fiber width of 0.1 to 20.0 μm. A method for producing microfibrous cellulose according to any one of the first to fifth aspects.

[0019] When the microfiber cellulose has the average fiber width of this embodiment, it has sufficient strength as a reinforcing material for resin.

[0020] [Seventh aspect] The denaturation step is carried out by heating for 1 second or more and 2 hours or less. A method for producing microfibrous cellulose according to any one of the first to sixth aspects.

[0021] If the heating time is within this range, the microfibrous cellulose produced will have excellent strength because it will be less damaged by heat.

[0022] [Eighth aspect] A kneading step is included in which the microfiber cellulose obtained by the manufacturing method of any one of the first to seventh aspects is kneaded with a resin to obtain a cellulose composite resin. A method for producing a cellulose composite resin comprising the steps of:

[0023] The microfiber cellulose produced by the above-mentioned embodiment is modified at a high modification rate to reduce hydrophilicity, and thus the repulsion when kneaded with a resin having hydrophobic properties is suppressed, resulting in a more homogeneous mixture.

[0024] [Ninth aspect] a modification step of modifying a cellulose raw material to obtain carbamate cellulose; The method includes a defibration step of defibrating the carbamate cellulose, The modification step is carried out by adding urea or a derivative thereof and a zwitterionic compound to a cellulose raw material and heating the mixture to 100 to 300°C. The fiber is obtained by the defibration process and has a crystallinity of 50 to 95%. Microfiber cellulose.

[0025] Since the microfibrous cellulose of the above embodiment has a crystallinity within the above range, it has sufficient strength as a reinforcing material for resin. Effect of the Invention

[0026] According to the present invention, there are provided microfibrous cellulose having an improved modification rate in a modification treatment, a method for producing microfibrous cellulose, and a method for producing a microfibrous cellulose composite resin. [Brief description of the drawings]

[0027] [Figure 1] FIG. 2 is an explanatory diagram of a method for producing microfiber cellulose. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Next, an embodiment of the present invention will be described. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.

[0029] The method for producing microfibrous cellulose in this embodiment includes a modification step of modifying a cellulose raw material to obtain carbamate cellulose, and a defibration step of defibrating the carbamate cellulose to obtain microfibrous cellulose, and the modification step is carried out by adding urea or a derivative thereof and a zwitterionic compound to the cellulose raw material and heating to 100 to 300° C. The process will be described in detail below.

[0030] (Denaturation process) The modification step is a step of modifying a cellulose raw material to obtain carbamate cellulose in which the hydroxyl groups of the cellulose raw material are replaced with carbamate groups. Examples of the form of the cellulose raw material used in the modification step include sheet-like pulp, slurry pulp, crushed pulp, fibrous pulp, etc. In particular, sheet-like pulp is preferred because it allows heat to be easily transferred to the entire cellulose raw material, resulting in good reaction efficiency for carbamate conversion and shortening the heating time.

[0031] An example of a reactant used to carbamate the cellulose raw material is urea or a derivative thereof. Urea or a derivative thereof is solid at room temperature and pressure, and chemically reacts with the cellulose raw material in a heated reaction system. However, in a heated reaction system, the cellulose raw material may be partially damaged by heat. Therefore, in this embodiment, the cellulose raw material is carbamate-converted without excessive heating by a method of chemically reacting the cellulose raw material in a reaction system containing urea or a derivative thereof and a zwitterionic compound. According to this method, urea or a derivative thereof and the zwitterionic compound behave like a deep eutectic solvent, so that carbamate-conversion is promoted without the need for excessive heating.

[0032] The chemical reaction between the cellulose raw material and urea or its derivatives is roughly as follows: When urea or its derivatives are heated, they are decomposed into isocyanic acid and ammonia as shown in the following reaction formula (1). Isocyanic acid is highly reactive and unstable, and for example, when it undergoes a chemical reaction as shown in the following reaction formula (2), the hydroxyl groups of cellulose are replaced with carbamate groups. NH2-CO-NH2→ HN=C=O + NH3…(1) Cell-OH + HN=C=O → Cell-O-CO-NH2…(2)

[0033] In a reaction system in which urea or its derivatives coexist with a zwitterionic compound, the reaction of the above reaction formula (1) is likely to occur, and more isocyanic acid is produced than in a reaction system without a zwitterionic compound. Since isocyanic acid easily reacts with the cellulose raw material, more cellulose substituted with carbamate groups is produced, which is thought to increase the modification rate of the cellulose raw material.

[0034] In the modification step, the temperature (heating temperature) at which the cellulose raw material to which urea or a derivative thereof and a zwitterionic compound have been added is heated is preferably 100° C. or higher, more preferably 140° C. or higher, and even more preferably 160° C. or higher. If the heating temperature is lower than 100° C., the carbamate reaction is unlikely to be promoted. On the other hand, the heating temperature is preferably 300° C. or lower, more preferably 280° C. or lower, and particularly preferably 260° C. or lower. If the heating temperature exceeds 300° C., the cellulose raw material may be decomposed or thermally modified, which may result in insufficient reinforcing effect of the resin.

[0035] In the modification step, the heating is preferably performed for 1 second or more, more preferably 5 seconds or more, and particularly preferably 10 seconds or more within the above heating temperature range. If the heating time is less than 1 second, the carbamate reaction may not be promoted. On the other hand, the heating is preferably performed for 2 hours or less, more preferably 1 hour or less, and particularly preferably 0.5 hours or less within the above heating temperature range. Since the carbamate reaction is almost completed by heating for 2 hours, there is little advantage to heating for more than that time. When the cellulose raw material is a sheet-like pulp, the heating can be performed for 60 seconds or less, more preferably 30 seconds or less, and particularly preferably 20 seconds or less within the above heating temperature range. When the cellulose raw material is a sheet-like pulp, heat is easily transferred, so the temperature difference within and between the pulps is small, and the carbamate reaction is promoted uniformly throughout the cellulose raw material and completed in a relatively short time.

[0036] In the modification step, in addition to the reaction temperature and reaction time, it is also preferable to adjust the pH in order to promote the chemical reaction. The pH is preferably 8 or more, more preferably an alkaline condition of 9 to 13. Alternatively, it is preferably an acidic or neutral condition of 7 or less, preferably 3 to 7. However, under alkaline conditions exceeding pH 13, the average fiber length of the cellulose raw material may be shortened, and the reinforcing effect of the resin may be deteriorated. On the other hand, under alkaline conditions of pH 9 to 13, the reactivity of the cellulose raw material is increased, the reaction to urea or its derivatives is promoted, and the carbamate reaction is efficiently carried out, so that the average fiber length of the cellulose raw material can be sufficiently secured. On the other hand, under acidic conditions of pH 6 or less, the reaction of decomposing urea or its derivatives into isocyanic acid and ammonia proceeds, the reaction to the cellulose raw material is promoted, and the carbamate reaction is efficiently carried out, so that the average fiber length of the cellulose raw material can be sufficiently secured. However, since a part of the cellulose may be acid-hydrolyzed under acidic conditions, it is preferable to perform the heat treatment under alkaline conditions. The pH can be adjusted by adding an acidic compound (eg, acetic acid, citric acid, etc.) or an alkaline compound (eg, sodium hydroxide, calcium hydroxide, etc.) to the mixture.

[0037] Examples of the heating method used in the modification step include a hot air method, a high-frequency heating method, a low-frequency heating method, a rotary kiln method, an induction heating roll method, an oil heating roll method, a far-infrared heating method, and a microwave method.

[0038] The product produced by the modification step may be washed before being subjected to the next step. This washing may be performed with water or the like. By this washing, the remaining unreacted urea or its derivatives, by-products, etc. can be removed.

[0039] The modification step can be carried out with or without the addition of an organic solvent. When an organic solvent is added, it is advisable to use an organic solvent that does not have reactivity with the hydroxyl group of the cellulose raw material. Examples of organic solvents include hydrocarbon solvents such as cyclohexane, toluene, and xylene, halogen solvents such as methylene chloride, chloroform, and dichloroethane, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, carboxylic acid solvents such as acetic acid, propionic acid, and butyric acid, and ether solvents such as tetrahydrofuran, diethyl ether, isopropyl ether, and 1,4-dioxane. However, when an organic solvent is added, the concentration of urea or its derivative in the reaction system is diluted, the encounter rate with the cellulose raw material as the reactant is reduced, and this may lead to a decrease in the modification rate of the carbamate group. Therefore, when an organic solvent is added, attention must be paid to the fraction of each reactant.

[0040] The reaction of the cellulose raw material with urea or its derivatives and a zwitterionic compound can be carried out, for example, as follows: First, the zwitterionic compound is mixed into an aqueous solution of urea or its derivatives to obtain solution A consisting of urea or its derivatives and the zwitterionic compound. The cellulose raw material is immersed in solution A, and the cellulose raw material and solution A are thoroughly mixed together.

[0041] Here, the inventors have found in the course of their research that the modification rate (carbamation rate) of the cellulose raw material depends to some extent on the concentration of the cellulose raw material in the entire reactant. The finding is that the modification rate tends to be higher when the concentration is high, but when the concentration is higher than a certain level, it is difficult to uniformly permeate the zwitterionic compound into urea or its derivatives. The reason for this tendency is unclear, but it is presumed that the heat transfer performance of the entire reaction system changes as the concentration of the cellulose raw material changes. The concentration of the cellulose raw material in the entire reactant is preferably 1.0 to 99.0 mass%, more preferably 10.0 to 90.0 mass%. If the concentration of the cellulose raw material is lower than 1.0 mass%, the modification rate decreases, and if it is higher than 99.0 mass%, the solution A and the cellulose raw material do not mix sufficiently. In particular, when the cellulose raw material is in a sheet form, carbamate-modified cellulose with a high modification rate can be obtained in a short time even if the concentration of the cellulose raw material in the entire reactant is 50 mass% or more. Here, the term "total reactants" refers to all of the substances used in the carbamate reaction in the modification step. For example, when a carbamate reaction is carried out using a cellulose raw material, urea or a derivative thereof, and a zwitterionic compound, the term refers to all of the cellulose raw material, urea or a derivative thereof, and the zwitterionic compound.

[0042] In the modification step, the carbamation is carried out in a state where the cellulose raw material, urea or a derivative thereof, and the zwitterionic compound are mixed. Prior to the carbamation, it is preferable to remove water from the entire reaction product by dehydration, heating, or the like. The mass ratio of urea or a derivative thereof to the zwitterionic compound is preferably 99 to 1:1 to 99, more preferably 9 to 1:1 to 9. If the mass ratio of urea or a derivative thereof to the zwitterionic compound is out of the above range, for example, if the amount of the zwitterionic compound is too large or too small relative to the amount of urea or a derivative thereof, the mixture containing urea or a derivative thereof and the zwitterionic compound is unlikely to behave as a deep eutectic solvent, and the modification rate of the cellulose raw material will be low.

[0043] Furthermore, when urea or a derivative thereof is added in an amount of 50 parts by mass or less per 100 parts by mass of water, the urea dissolves sufficiently in the water and uniformly penetrates into the cellulose raw material, which is preferable because it increases the modification rate of the cellulose raw material.

[0044] When a carbamate reaction is carried out, the mixing ratio of the cellulose raw material and urea or a derivative thereof is preferably 1 to 1,000 parts by mass, more preferably 10 to 100 parts by mass, of the cellulose raw material per 1 part by mass of urea or a derivative thereof, calculated as solid content. If the cellulose raw material is less than 1 part by mass per 1 part by mass of urea or a derivative thereof, the amount of urea or a derivative thereof is excessive, and if it exceeds 1,000 parts by mass, the cellulose raw material and the urea or a derivative thereof may not be mixed sufficiently.

[0045] Examples of urea or a derivative thereof used in the modification step include one or more selected from urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, and compounds in which hydrogen atoms of urea are substituted with alkyl groups, etc. Urea is particularly preferred because of its excellent reactivity and workability.

[0046] The zwitterionic compound used in the modification step is a compound having both positive and negative charges in one molecule. Examples of molecules having a positive charge include quaternary ammonium cation compounds, sulfonium compounds, and phosphonium compounds, and examples of molecules having a negative charge include carbonyl compounds, sulfonyl compounds, phosphonyl compounds, and chlorides. Specific examples of the zwitterionic compound include betaines (e.g., alkyl betaines, amido betaines, sulfo betaines, and alkyl sulfo betaines), glycine, sulfamic acid, choline chloride, trimethyl glycine, sydnone, amine oxides, azoxy compounds, nitrile oxides, nitrile imides, phosphine oxides, phosphorus ylides, 3-hydroxy-2-(trimethyl amino) propanoic acid ions, dimethyl (2-hydroxyethyl) amino acetate, and derivatives thereof. In terms of ease of handling, ease of cleaning, and ease of deep eutectic solventization, trimethyl glycine or its derivatives are particularly preferred.

[0047] (defibration process) The defibration of the cellulose raw material can be carried out by beating the cellulose raw material using, for example, a homogenizer such as a beater, a high-pressure homogenizer, or a high-pressure homogenizer, a stone mill-type friction machine such as a grinder or a grinder, a single-shaft kneader, a multi-shaft kneader, a kneader refiner, a jet mill, etc. In particular, the use of a refiner or a jet mill is preferred because damage to the fibers can be suppressed and the fibers become homogeneous.

[0048] The average fiber length (average length of single fiber) of the microfiber cellulose obtained by defibrating the cellulose raw material is preferably 0.10 to 2.00 mm, more preferably 0.12 to 1.50 mm, and particularly preferably 0.15 to 1.00 mm. If the average fiber length is less than 0.10 mm, a three-dimensional network between the fibers cannot be formed, and the flexural modulus of the composite resin may decrease, and the reinforcing effect may not be improved. On the other hand, if the average fiber length exceeds 2.00 mm, the reinforcing effect may be insufficient because the length is the same as that of the raw pulp.

[0049] The average fiber width (also referred to as the average fiber diameter) of the microfiber cellulose is not particularly limited, but it is preferable to defibrate the microfiber cellulose (microfibrillated cellulose) so that the average fiber width is preferably 0.1 to 20 μm, more preferably 0.2 to 15 μm, and preferably more than 0.3 to 10 μm. The microfiber cellulose having an average fiber width in the above range is suitable for reinforcing the resin used in compounding, and the strength of the compound resin produced from the microfiber cellulose is significantly improved. In this embodiment, the cellulose defibrated to an average fiber width in the above range is called microfiber cellulose, microfibrillated cellulose, or MFC. If the average fiber width of the microfiber cellulose is less than 0.1 μm, it can be said to be equivalent to cellulose nanofiber, and there is a risk that the effect of improving the strength of the resin (especially the bending modulus) is not fully exhibited. In addition, it takes a lot of time and energy to defibrate, which is uneconomical. Furthermore, when the fibers are made into a slurry, the dewaterability is deteriorated. The deterioration of dewaterability requires a large amount of energy for drying when obtaining a dried fiber, and the application of excessive energy may cause damage to the fiber, and the effect of improving the strength of the resin may not be achieved. In particular, when the average fiber width is less than 0.10 μm, the thermal decomposition temperature drops significantly, so the heat resistance drops and it becomes unsuitable for kneading with resin. On the other hand, when the average fiber width of microfiber cellulose exceeds 20 μm, there is almost no difference from pulp, and the reinforcing effect may not be obtained.

[0050] In this embodiment, the average fiber width of the microfiber cellulose is measured as follows. First, 100 ml of an aqueous dispersion of fine fibers with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 3,000 to 30,000 times depending on the width of the fibers that constitute it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersections of the diagonal lines are arbitrarily drawn. Furthermore, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of the measured values ​​is taken as the average fiber width.

[0051] As mentioned above, microfiber cellulose can be obtained by defibrating (refining) cellulose raw materials. As the raw pulp used for the cellulose raw material, one or more types can be selected from wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fibers, etc., and waste paper pulp (DIP) made from recycled waste paper, broke, etc. Note that the above various raw materials may be in the form of a pulverized material (powdered material) called cellulose-based powder, for example. However, in order to avoid the inclusion of impurities as much as possible, it is preferable to use wood pulp as the raw pulp. As the wood pulp, one or more types can be selected from chemical pulps such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP), mechanical pulp (TMP), etc.

[0052] The hardwood kraft pulp can be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, semi-bleached hardwood kraft pulp, etc. The softwood kraft pulp can be bleached softwood kraft pulp, unbleached softwood kraft pulp, semi-bleached softwood kraft pulp, etc.

[0053] The mechanical pulp can be used without any particular limitation, and for example, one or more types can be selected from stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), chemi-ground pulp (CGP), thermo-ground pulp (TGP), ground pulp (GP), thermo-mechanical pulp (TMP), chemi-thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermo-mechanical pulp (BTMP), etc.

[0054] The cellulose raw material (raw pulp) can be pretreated by a chemical method prior to defibration. Examples of pretreatment by a chemical method include hydrolysis of polysaccharides with an acid (acid treatment), hydrolysis of polysaccharides with an enzyme (enzyme treatment), swelling of polysaccharides with an alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), reduction of polysaccharides with a reducing agent (reduction treatment), and the like. Among these treatments, enzyme treatment is particularly preferred because it does not damage the fibers. It is preferable to carry out one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment in addition to the enzyme treatment, since defibration is easily achieved.

[0055] The pretreatment is a treatment for facilitating defibration of the cellulose raw material (raw pulp), and may be carried out before the modification step of carbamate-converting the cellulose raw material, or may be carried out after the modification step and then the defibration step. The enzyme treatment will be described in detail below.

[0056] As the enzyme used in the enzymatic treatment, it is preferable to use at least one of cellulase enzymes and hemicellulase enzymes, and more preferably to use both in combination. The use of these enzymes makes it easier to defibrate the cellulose raw material. Note that cellulase enzymes cause the decomposition of cellulose in the presence of water. Also, hemicellulase enzymes cause the decomposition of hemicellulose in the presence of water.

[0057] Examples of cellulase enzymes that can be used include enzymes produced by the genera Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycetes), Trametes (basidiomycetes), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycetes), Streptomyces (bacteria), and Pseudomonas (bacteria). These cellulase enzymes are available as reagents or commercially available products. Examples of commercially available products include Cellulose T2 (manufactured by HPI), Meicerase (manufactured by Meiji Seika Kaisha), Novozym 188 (manufactured by Novozym), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).

[0058] As the cellulase enzyme, EG (endoglucanase) and CBH (cellobiohydrolase) can be used. EG and CBH can be used alone or in combination. They can also be used in combination with hemicellulase enzymes.

[0059] Examples of hemicellulase enzymes that can be used include xylanase, which is an enzyme that breaks down xylan, mannase, which is an enzyme that breaks down mannan, and arabanase, which is an enzyme that breaks down araban. Also, pectinase, which is an enzyme that breaks down pectin, can be used.

[0060] Hemicellulose is a polysaccharide, excluding pectins, found between cellulose microfibrils in plant cell walls. Hemicellulose is diverse and differs depending on the type of wood and between the layers of the cell wall. In the secondary walls of softwoods, glucomannan is the main component, while in the secondary walls of hardwoods, 4-O-methylglucuronoxylan is the main component. Therefore, when obtaining fine fibers from softwood bleached kraft pulp (NBKP), it is preferable to use mannase. Also, when obtaining fine fibers from hardwood bleached kraft pulp (LBKP), it is preferable to use xylanase.

[0061] The amount of enzyme added to the cellulose raw material is determined by, for example, the type of enzyme, the type of wood used as the raw material (coniferous or broadleaf), the type of mechanical pulp, etc. However, the amount of enzyme added to 100 parts by mass of the cellulose raw material is preferably 0.1 to 3 parts by mass, more preferably 0.3 to 2.5 parts by mass, and particularly preferably 0.5 to 2 parts by mass. If the amount of enzyme added is less than 0.1 part by mass, the effect of adding the enzyme may not be sufficiently obtained. On the other hand, if the amount of enzyme added is more than 3% by mass, cellulose may be saccharified, and the yield of the cellulose raw material may decrease. In addition, there is also a problem that the effect improvement corresponding to the increase in the amount added cannot be recognized.

[0062] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak acidic range (pH = 3.0 to 6.9) from the viewpoint of the reactivity of the enzyme reaction, whereas when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weak alkaline range (pH = 7.1 to 10.0).

[0063] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., regardless of whether a cellulase enzyme or a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is easily activated and the enzyme treatment is completed in a short time. On the other hand, if the temperature during the enzyme treatment is 70° C. or lower, the deactivation of the enzyme can be prevented.

[0064] The time for the enzyme treatment depends on, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. However, the time for the enzyme treatment is generally 0.5 to 24 hours.

[0065] After the enzyme treatment, it is preferable to inactivate the enzyme. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) and a method of adding hot water at 80 to 100°C.

[0066] Next, the alkali treatment method will be described. When the pulp is treated with alkali prior to defibration, the hydroxyl groups of the hemicellulose and cellulose contained in the pulp are partially dissociated and the molecules are anionized, weakening the intra- and intermolecular hydrogen bonds and promoting the dispersion of the cellulose raw material during defibration.

[0067] Examples of the alkali used in the alkali treatment include organic alkalis such as sodium hydroxide, lithium hydroxide, potassium hydroxide, an aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide. However, from the viewpoint of production costs, it is preferable to use sodium hydroxide.

[0068] An example of pretreatment prior to defibration has been described above. Pretreatment can reduce the water retention of microfibrous cellulose, increase the crystallinity, and increase the homogeneity. Low water retention of microfibrous cellulose makes it easier to dehydrate, improving the dehydration of the cellulose raw material slurry. Pretreatment also decomposes the hemicellulose and amorphous regions of cellulose contained in pulp. Decomposition of the amorphous regions can reduce the energy required for defibration, improving the uniformity and dispersibility of the defibrated microfibrous cellulose. However, since pretreatment reduces the aspect ratio of microfibrous cellulose, excessive pretreatment is preferably avoided when using it as a resin reinforcing material.

[0069] The average fiber length of the cellulose raw material is preferably 0.50 to 5.00 mm. If the average fiber length is less than 0.50 mm, the microfiber cellulose obtained by defibration may not sufficiently reinforce the resin. On the other hand, if the average fiber length is more than 5.00 mm, the energy required for defibrating the cellulose raw materials may be large, which may be disadvantageous in terms of production costs.

[0070] The average fiber length of the cellulose raw material can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, defibrating it, and the like.

[0071] In this embodiment, the average fiber length of the cellulose raw material is a value measured using a fiber analyzer "FS5" manufactured by Valmet.

[0072] When the cellulose raw material is in the form of a sheet, the basis weight of the sheet is preferably 10 to 1,000 g / m 2 , more preferably 50 to 800 g / m 2 The basis weight of the cellulose raw material is preferably 1,000 g / m 2 If the basis weight is in the above range, the urea can easily penetrate into the cellulose, and sufficient carbamate modification can be achieved.

[0073] The fineness ratio of the microfiber cellulose obtained by defibration is preferably 10% or more, more preferably 20 to 90%, and particularly preferably 30 to 80%. If the fineness ratio exceeds 90%, the proportion of homogeneous fibers is high, and the microfiber cellulose is likely to aggregate in the composite resin, making it difficult to contribute to the reinforcing effect. However, if the fineness ratio is less than 10%, the bending elastic modulus may be insufficient.

[0074] It is also more preferable to set the fineness ratio of the cellulose raw material before defibration within a specified range. Specifically, the fineness ratio of the cellulose raw material before defibration is preferably 1% or more, more preferably 3 to 20%, and particularly preferably 5 to 18%. If the fineness ratio of the cellulose raw material before defibration is within the above range, it is considered that even if the microfiber cellulose is defibrated to have a fineness ratio of 30% or more, the damage to the fibers is small and the reinforcing effect of the resin is improved.

[0075] The fineness ratio can be adjusted by pretreatment such as enzyme treatment. However, when enzyme treatment is performed, the bond state within the fiber may be partially destroyed, and the reinforcing effect of the resin may be reduced. Therefore, it is better to reduce the enzyme addition rate, for example, preferably 2% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. Another option is not to perform enzyme treatment (addition amount 0% by mass).

[0076] "Fine ratio" refers to the mass ratio of pulp fibers with a fiber length of 0.2 mm or less. This fine ratio can be measured using the fiber analyzer "FS5" manufactured by Valmet. The fiber analyzer "FS5" can measure the length and width of cellulose fibers with high accuracy by analyzing the images of diluted cellulose fibers passing through the measurement cell inside the fiber analyzer.

[0077] The aspect ratio of the microfibrous cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be sufficiently constructed, and therefore even if the average fiber length is 0.10 mm or more, the reinforcing effect may be insufficient. On the other hand, if the aspect ratio exceeds 15,000, the microfibrous cellulose may be entangled more frequently, resulting in insufficient dispersion in the resin.

[0078] In this embodiment, the aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. The larger the aspect ratio, the more points at which snagging occurs, and therefore the reinforcement effect is improved, but on the other hand, it is thought that the ductility of the resin is reduced by the amount of snagging.

[0079] The fibrillation rate of the microfibrous cellulose is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate exceeds 30.0%, the number of bonds between the microfibrous cellulose and water molecules per unit area is large, which may make dehydration difficult. On the other hand, if the fibrillation rate is below 1.0%, the fibrils are less likely to be bonded to water molecules, and the three-dimensional network formed by hydrogen bonds may not be strong.

[0080] In this embodiment, the fibrillation rate refers to a value measured using a fiber analyzer "FS5" manufactured by Valmet.

[0081] The crystallinity of the microfiber cellulose is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, the strength of the fiber itself may decrease, and the strength of the resin may not be improved. If the crystallinity is less than 50%, the heat resistance of the carbamate-modified microfiber cellulose may be insufficient. If the crystallinity is low, the thermal decomposition reaction of the microfiber cellulose will immediately proceed due to heat applied from the outside. On the other hand, the crystallinity of the microfiber cellulose is preferably 95% or less, more preferably 90% or less. If the crystallinity is more than 95%, the amount of hydrogen bonds within and between cellulose molecules increases, resulting in poor dispersibility.

[0082] The crystallinity of the microfibrous cellulose can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, and refining it.

[0083] In this embodiment, the crystallinity is a value measured in accordance with JIS K 0131 (1996).

[0084] The pulp viscosity of the microfiber cellulose is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of the microfiber cellulose is less than 2 cps, the dispersibility of the microfiber cellulose may deteriorate.

[0085] In this embodiment, the pulp viscosity is a value measured in accordance with TAPPI T230.

[0086] The freeness of the microfiber cellulose is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness of the microfiber cellulose exceeds 500 ml, the strength improving effect of the resin may not be sufficiently obtained.

[0087] In the present embodiment, the freeness is a value measured in accordance with JIS P8121-2 (2012).

[0088] The zeta potential of an aqueous dispersion of microfibrous cellulose with a solid content of 1% is preferably -150 to 20 mV, more preferably -100 to 0 mV. If the zeta potential is lower than -150 mV, the compatibility with the resin may be significantly reduced, resulting in insufficient reinforcing effect. On the other hand, if the zeta potential is higher than 20 mV, the dispersion stability may be reduced.

[0089] The water retention of the microfibrous cellulose is preferably 50 to 400%, more preferably 90 to 350%. If the water retention is less than 50%, the water retention is the same as that of the cellulose raw material, and the reinforcing effect may be insufficient. On the other hand, if the water retention exceeds 400%, it becomes difficult to dry. The water retention of the microfibrous cellulose tends to decrease as the modification rate of the carbamate group in the microfibrous cellulose increases, so the water retention can be adjusted to a desired value by adjusting the modification rate.

[0090] The water retention of the microfiber cellulose can be adjusted as desired by, for example, selecting the raw pulp, pre-treating it, defibrating it, and the like.

[0091] In this embodiment, the water retention is a value measured in accordance with JAPAN TAPPI No. 26 (2000).

[0092] In this embodiment, the carbamate-modified microfiber cellulose has a carbamate group. Here, the carbamate group is a group represented by -O-CO-NH-, and examples thereof include groups represented by -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. The carbamate group can be represented by the following structural formula (1).

[0093] [ka]

[0094] Here, R (R1, R2) are each independently at least one of a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and derivatives thereof.

[0095] Examples of the saturated linear hydrocarbon group include linear alkyl groups having 1 to 10 carbon atoms, such as methyl, ethyl, and propyl groups. Examples of the saturated branched hydrocarbon group include branched alkyl groups having 3 to 10 carbon atoms, such as isopropyl, sec-butyl, isobutyl, and tert-butyl groups. Examples of the saturated cyclic hydrocarbon group include cycloalkyl groups such as cyclopentyl, cyclohexyl, and norbornyl groups. Examples of the unsaturated linear hydrocarbon group include linear alkenyl groups having 2 to 10 carbon atoms, such as ethenyl, propen-1-yl, and propen-3-yl groups, and linear alkynyl groups having 2 to 10 carbon atoms, such as ethynyl, propyn-1-yl, and propyn-3-yl groups. Examples of the unsaturated branched hydrocarbon group include branched alkenyl groups having 3 to 10 carbon atoms, such as propen-2-yl, buten-2-yl, and buten-3-yl, and branched alkynyl groups having 4 to 10 carbon atoms, such as butyn-3-yl. Examples of the aromatic group include phenyl, tolyl, xylyl, and naphthyl. Examples of the derived group include the above-mentioned saturated linear hydrocarbon group, saturated branched hydrocarbon group, saturated cyclic hydrocarbon group, unsaturated linear hydrocarbon group, unsaturated branched hydrocarbon group, and aromatic group in which one or more hydrogen atoms are substituted with a substituent (e.g., hydroxyl group, carboxyl group, halogen atom, etc.).

[0096] In microfiber cellulose having a carbamate group (introduced with a carbamate group), some or all of the polar hydroxyl groups are replaced with carbamate groups, which are relatively non-polar groups. Microfiber cellulose having a carbamate group is more non-polar, i.e., hydrophobic, than microfiber cellulose that is not carbamate-modified as a single entity, and therefore has a weak repulsion with resins and the like that have hydrophobic properties. Therefore, microfiber cellulose having a carbamate group mixed with a resin is less likely to aggregate with each other, has good dispersibility, and adheres to the resin. In addition, a slurry of microfiber cellulose having a carbamate group has low viscosity and good handling properties.

[0097] The modification rate of the carbamate group to the hydroxyl group of the microfiber cellulose (carbamation rate) is preferably 0.1 to 5.0 mmol / g, more preferably 0.5 to 3.0 mmol / g. When the modification rate is 0.1 mmol / g or more, the effect of introducing the carbamate group, particularly the effect of improving the bending modulus of the resin, can be reliably achieved. This is because microfiber cellulose with a modification rate of 0.1 mmol / g or more has a reduced hydrophilicity, so that the repulsion with the resin is weak and the resin is appropriately dispersed therein, so that the composite resin produced is less likely to have localized strength variations and is homogeneous. On the other hand, when the modification rate of the carbamate group exceeds 5.0 mmol / g, the strength of the composite resin decreases. This is because the microfiber cellulose forms a strong three-dimensional network by hydrogen bonding, but when the modification rate of the carbamate group is too high, the hydroxyl group that contributes to the formation of the three-dimensional network is relatively reduced, making it difficult to form a strong three-dimensional network.

[0098] In this embodiment, the modification rate of carbamate groups (mmol / g) refers to the amount of carbamate groups contained in 1 g of microfiber cellulose having carbamate groups. The modification rate of carbamate groups is calculated by measuring the N atoms present in the carbamate-modified pulp by the Kjeldahl method and calculating the carbamate conversion rate per unit mass. Cellulose is a polymer with anhydroglucose as a structural unit, and has three hydroxyl groups per structural unit.

[0099] (slurry) The produced microfiber cellulose is preferably dispersed in an aqueous medium to form a dispersion (slurry) for easy storage and handling. The aqueous medium is particularly preferably entirely water, but an aqueous medium in which part of the medium is a liquid compatible with water can be used. As the liquid, lower alcohols having 3 or less carbon atoms can be used.

[0100] The solid content of the slurry is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass. If the solid content is less than 0.1% by mass, a large amount of slurry must be prepared for the production of the composite resin, which is troublesome and may require excessive energy for dehydration and drying. On the other hand, if the solid content is more than 10.0% by mass, the fluidity of the slurry itself decreases, making it difficult to mix uniformly and making it difficult to use.

[0101] (Acid-modified resin) The microfiber cellulose is preferably mixed with an acid-modified resin. When the acid-modified resin is mixed, the acid groups are ionically bonded to some or all of the carbamate groups. This ionic bond improves the reinforcing effect of the resin.

[0102] Examples of the acid-modified resin include acid-modified polyolefin resin, acid-modified epoxy resin, and acid-modified styrene-based elastomer resin. However, it is preferable to use an acid-modified polyolefin resin. The acid-modified polyolefin resin is a copolymer of an unsaturated carboxylic acid component and a polyolefin component.

[0103] As the polyolefin component, for example, one or more types may be selected from polymers of alkenes such as ethylene, propylene, butadiene, isoprene, etc. However, it is preferable to use a polypropylene resin, which is a polymer of propylene.

[0104] As the unsaturated carboxylic acid component, for example, one or more selected from maleic anhydrides, phthalic anhydrides, itaconic anhydrides, citraconic anhydrides, citric anhydrides, etc. can be used. However, it is preferable to use maleic anhydrides. In other words, it is preferable to use maleic anhydride-modified polypropylene resin.

[0105] The amount of the acid-modified resin is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, relative to 100 parts by mass of the microfiber cellulose. In particular, when the acid-modified resin is a maleic anhydride-modified polypropylene resin, the amount is preferably 1 to 200 parts by mass, more preferably 10 to 100 parts by mass. If the amount of the acid-modified resin is less than 0.1 parts by mass, the strength is not sufficiently improved. On the other hand, if the amount is more than 1,000 parts by mass, the strength tends to decrease due to the excessive amount.

[0106] The weight average molecular weight of the maleic anhydride modified polypropylene is, for example, 1,000 to 100,000, and preferably 3,000 to 50,000.

[0107] The acid value of the maleic anhydride modified polypropylene is preferably 0.5 mgKOH / g or more and 100 mgKOH / g or less, and more preferably 1 mgKOH / g or more and 50 mgKOH / g or less.

[0108] Furthermore, the MFR (melt flow rate) of the acid-modified resin is preferably 2000 g / 10 min (190° C. / 2.16 kg) or less, more preferably 1500 g / 10 min or less, and particularly preferably 500 g / 10 min or less. If the MFR exceeds 2000 g / 10 min, the dispersibility of the microfiber cellulose may decrease.

[0109] The acid value is measured in accordance with JIS-K2501 by titration with potassium hydroxide, and the MFR is measured in accordance with JIS-K7210 by placing a load of 2.16 kg at 190°C and measuring the weight of the sample that flows out in 10 minutes.

[0110] (Dispersant) The microfiber cellulose of this embodiment is preferably mixed with a dispersant. When a dispersant is mixed with the microfiber cellulose, the microfiber cellulose is less likely to aggregate with each other. This is because the dispersant has the function of inhibiting hydrogen bonding between the microfiber cellulose. The presence of a dispersant improves the dispersibility of the microfiber cellulose in the resin when the microfiber cellulose and the resin are kneaded. The dispersant also plays a role in improving the compatibility of the microfiber cellulose and the resin.

[0111] As the dispersant, a compound having an amine group and / or a hydroxyl group in an aromatic group, and a compound having an amine group and / or a hydroxyl group in an aliphatic group are preferred.

[0112] Examples of compounds having an amine group and / or a hydroxyl group in an aromatic group include anilines, toluidines, trimethylanilines, anisidines, tyramines, histamines, tryptamines, phenols, dibutylhydroxytoluenes, bisphenol A, cresols, eugenols, gallic acids, guaiacols, picric acids, phenolphthaleins, serotonins, dopamines, adrenalines, noradrenalines, thymols, tyrosines, salicylic acids, methyl salicylates, a Examples of such alcohols include varnish alcohols, salicylic alcohols, sinapyl alcohols, diphenidols, diphenylmethanols, cinnamyl alcohols, scopolamines, tryptophols, vanillyl alcohols, 3-phenyl-1-propanols, phenethyl alcohols, phenoxyethanols, veratryl alcohols, benzyl alcohols, benzoins, mandelic acids, mandelonitriles, benzoic acids, phthalic acids, isophthalic acids, terephthalic acids, mellitic acids, and cinnamic acids.

[0113] Examples of compounds having an amine group and / or a hydroxyl group in an aliphatic group include capryl alcohols, 2-ethylhexanols, pelargonic alcohols, capric alcohols, undecyl alcohols, lauryl alcohols, tridecyl alcohols, myristyl alcohols, pentadecyl alcohols, cetanols, stearyl alcohols, elaidyl alcohols, oleyl alcohols, linoleyl alcohols, methylamines, dimethylamines, trimethylamines, ethylamines, diethylamines, ethylenedi ... ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines, ethylamines Examples of such acids include triethanolamines, N,N-diisopropylethylamines, tetramethylethylenediamines, hexamethylenediamines, spermidines, spermines, amantadines, formic acids, acetic acids, propionic acids, butyric acids, valeric acids, caproic acids, enanthic acids, caprylic acids, pelargonic acids, capric acids, lauric acids, myristic acids, palmitic acids, margaric acids, stearic acids, oleic acids, linoleic acids, linolenic acids, arachidonic acids, eicosapentaenoic acids, docosahexaenoic acids, and sorbic acids.

[0114] The amount of the dispersant mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, relative to 100 parts by mass of the microfiber cellulose. If the amount of the dispersant mixed is less than 0.1 parts by mass, the effect of adding the dispersant is weak, and the strength of the resin may not be sufficiently improved. On the other hand, if the amount mixed is more than 1,000 parts by mass, the dispersibility of the microfiber cellulose may decrease due to the excess dispersant.

[0115] The acid-modified resin described above is intended to improve compatibility by forming ionic bonds between the acid groups and the carbamate groups of the microfibrous cellulose, thereby enhancing the reinforcing effect, and is easily dispersed together with the resin used for kneading due to its large molecular weight. The dispersant prevents aggregation by interposing between the hydroxy groups of the microfibrous cellulose, and since its molecular weight is smaller than that of the acid-modified resin, it can enter narrow spaces between the microfibrous cellulose that the acid-modified resin cannot enter, thereby improving the dispersibility of the microfibrous cellulose. Therefore, the molecular weight of the acid-modified resin is preferably 2 to 2,000 times, and more preferably 5 to 1,000 times, the molecular weight of the dispersant.

[0116] (powder) The microfiber cellulose of this embodiment is preferably mixed with a powder. By mixing with a powder, the microfiber cellulose can be made into a form that suppresses aggregation and can exhibit the reinforcing properties of the resin. The moisture content of the microfiber cellulose should be adjusted to a predetermined range until it is combined with the resin. If the moisture content exceeds the range, the microfiber cellulose will be hydrogen-bonded to each other and aggregate during the process of removing the aqueous medium, and the dispersibility with the resin will deteriorate, and the effect of reinforcing the resin may not be fully exhibited.

[0117] The powder used should preferably be poorly reactive with microfiber cellulose. Poorly reactive means that chemical reactions, such as covalent bonds, ionic bonds, metallic bonds, hydrogen bonds, and bonds due to van der Waals forces, are difficult to promote. It can also be said that the activation energy of the powder when it chemically reacts with the microfiber cellulose exceeds 100 kJ / mol.

[0118] The powder can be selected from inorganic powders and resin powders, but inorganic powders are preferable. Inorganic powders are preferable because they have a reaction suppressing effect because they are difficult to dissociate the carboxyl groups of cellulose fibers into hydroxide ions. In particular, inorganic powders are advantageous in terms of operation. For example, the moisture content of a microfiber cellulose-containing material can be adjusted by directly applying a mixture of microfiber cellulose and powder to a metal drum, which is a heat source, to dry the mixture, or by heating the mixture without directly contacting the heat source. However, when resin powder is used, there is a concern that when the resin powder is dried by contacting it with a heated metal plate (e.g., Yankee dryer, cylinder dryer, etc.), a film is formed on the surface of the metal plate, which deteriorates heat conduction and significantly reduces drying efficiency, and inorganic powders are less likely to cause such problems.

[0119] The average particle size of the powder is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size exceeds 10,000 μm, the powder may enter the gaps between the cellulose fibers and the effect of inhibiting aggregation may be lost. If the average particle size is less than 1 μm, the powder particle size is too small compared to the cellulose fibers, and the effect of inhibiting aggregation between the cellulose fibers may not be exhibited.

[0120] The resin powder plays a role of physically interposing between the cellulose fibers to inhibit hydrogen bonding and improve the dispersibility of the microfiber cellulose. On the other hand, the above-mentioned acid-modified resin improves compatibility by ionic bonding between the acid group and the carbamate group of the microfiber cellulose, thereby enhancing the reinforcing effect. The dispersant has the same effect of inhibiting hydrogen bonding between the microfiber cellulose, but since the particle size of the resin powder is on the micron order, it physically interposes and suppresses hydrogen bonding. Although the resin powder has lower dispersibility than the dispersant, the resin powder itself melts and forms a matrix, so it does not contribute to a decrease in physical properties. On the other hand, the dispersant has a particle size at the molecular level and is extremely small, so it covers the microfiber cellulose to inhibit hydrogen bonding, and is highly effective in improving the dispersibility of the microfiber cellulose. However, it may remain in the resin and cause a decrease in physical properties.

[0121] The average particle size of a powder is the median diameter calculated from the volume-based particle size distribution measured using a particle size distribution measuring device (e.g., a laser diffraction / scattering particle size distribution measuring device manufactured by Horiba, Ltd.) while the powder is either as is or in the form of a water dispersion.

[0122] Examples of inorganic powders include simple substances, oxides, hydroxides, carbonates, sulfates, silicates, sulfites, and various clay minerals made of compounds of metal elements in Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon. Specific examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, heavy calcium carbonate, light calcium carbonate, aluminum borate, alumina, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay, wollastonite, glass beads, glass powder, silica gel, dry silica, colloidal silica, silica sand, silica stone, quartz powder, diatomaceous earth, white carbon, and glass fiber. A plurality of these inorganic fillers may be contained. In addition, the filler may be one contained in waste paper pulp, or may be a so-called regenerated filler obtained by regenerating inorganic matter in papermaking sludge.

[0123] It is preferable to use at least one inorganic powder selected from calcium carbonate, talc, white carbon, clay, calcined clay, titanium dioxide, aluminum hydroxide, and regenerated fillers, which are preferably used as fillers or pigments for papermaking, more preferably at least one selected from calcium carbonate, talc, and clay, and particularly preferably at least one of light calcium carbonate and heavy calcium carbonate. Calcium carbonate, talc, and clay have the advantage that they are easy to compound with a matrix such as a resin, and are versatile inorganic materials, so that there are few limitations on their applications. Furthermore, calcium carbonate is particularly preferable. Light calcium carbonate powder can be controlled in size and shape as desired, and can be molded to fit into gaps according to the size and shape of the cellulose raw material, making it easier to produce the effect of suppressing the aggregation of the cellulose raw material. In addition, heavy calcium carbonate is amorphous, so even if fibers of various sizes are present in the slurry, it can enter the gaps and suppress the aggregation of the cellulose raw material during the process in which the aqueous medium is removed and the fibers aggregate during the drying process.

[0124] The resin used for the resin powder is not particularly limited and various resins can be used. However, it is preferable to use the same resin as that used for obtaining the composite resin, since a single resin can be used for a variety of purposes.

[0125] The mixing ratio of the powder is preferably 0.01 to 99 parts by mass, more preferably 0.05 to 19 parts by mass, and particularly preferably 0.1 to 9 parts by mass, per part by mass of the microfiber cellulose. If the mixing ratio of the powder to the microfiber cellulose is less than 0.01 parts by mass, there is a risk that the powder will be insufficient and will enter the gaps in the cellulose raw material to suppress aggregation, and if the mixing ratio exceeds 99 parts by mass, the fibers will be buried in the powder, which may cause problems in the kneading process of the microfiber cellulose and the resin.

[0126] The inorganic powder and the resin powder exemplified as the powder can be used in combination. When the inorganic powder and the resin powder are used in combination, even if the inorganic powder and the resin powder are mixed under conditions in which either one of them aggregates, the effect of preventing aggregation is exhibited by mixing both the inorganic powder and the resin powder. In general, a powder with a small particle size has a relatively large surface area and is subject to the action of intermolecular forces in addition to the action of gravity, and tends to aggregate easily, but when the inorganic powder and the resin powder are used in combination, aggregation between the powders with small particle sizes is suppressed. From this viewpoint, when the inorganic powder and the resin powder are used in combination, the ratio of the average particle size of the inorganic powder to the average particle size of the resin powder is preferably 1:0.1 to 1:10000, more preferably 1:1 to 1:1000.

[0127] The method for producing microfibrous cellulose of this embodiment will be described with reference to Fig. 1. A cellulose raw material C is placed in a container 10, urea or its derivative U, and a zwitterionic compound B are added and mixed, and the mixture is dried and heated P to carry out a modification step, thereby obtaining modified cellulose fibers. The obtained cellulose fibers are then subjected to a defibration step 20 to obtain microfibrous cellulose X.

[0128] (Method of manufacturing composite resin) The mixture of microfiber cellulose, acid-modified resin, dispersant, powder, etc., to be kneaded with resin, is preferably dried to a moisture content of less than 18%. This dried product is preferably pulverized into a powder. When the product is in the form of a powder, the coloring of the microfiber cellulose composite resin obtained by kneading with resin is reduced. In general, when a composite resin is produced from a cellulose raw material and a resin, the composite resin has a yellowish color. However, the composite resin produced from the powder has a color close to the original color of the resin. In addition, if the product is in the form of a powder, it is easily dried, and there is no need to dry the microfiber cellulose when kneading with resin, and the thermal efficiency of kneading is good. When a powder or a dispersant is mixed in the mixture, there is a low risk that the microfiber cellulose (microfiber cellulose) will not be redispersed even if the mixture is dried.

[0129] When the mixture is dried to obtain a dried product, it is preferable to dehydrate the mixture before drying. This dehydration can be performed using a dehydration device. Examples of the dehydration device include a belt press, a screw press, a filter press, a twin roll, a twin wire former, a valveless filter, a center disk filter, a membrane treatment, and a centrifuge.

[0130] The mixture or the dehydrated product can be dried using a drying device, such as a rotary kiln dryer, a disk dryer, an airflow dryer, a media flow dryer, a spray dryer, a drum dryer, a screw conveyor dryer, a paddle dryer, a single-shaft kneading dryer, a multi-shaft kneading dryer, a vacuum dryer, or an agitator dryer.

[0131] The dried or dehydrated material can be pulverized into a powder using a pulverizer, such as a bead mill, kneader, disperser, twist mill, cut mill, or hammer mill.

[0132] The powder preferably has an average particle size of 10,000 μm or less, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size exceeds 10,000 μm, there is a risk that the powder may not be dried easily. On the other hand, although it is not necessary to strictly determine the lower limit of the average particle size, for example, making the average particle size less than 1 μm is not economical because it requires a large amount of energy.

[0133] The average particle size of the powdery material can be controlled by classification using a classification device (filter, cyclone, etc.).

[0134] The bulk density of the mixture (powder material) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. If the bulk density exceeds 1.0, the microfiber cellulose will be strongly aggregated due to hydrogen bonds between them, making it difficult to disperse the microfiber cellulose in the resin. On the other hand, if the bulk density is less than 0.03, the mixture and the microfiber cellulose will be separated by gravity during the kneading process, and excellent dispersibility will not be maintained. A composite resin with excellent reinforcing effect or a composite resin with poor reinforcing effect may be produced, and the product may not be homogeneous.

[0135] The bulk density is a value measured in accordance with JIS K7365.

[0136] The moisture content of the mixture (material containing microfiber cellulose) is preferably less than 18%, more preferably 0 to 17%, and particularly preferably 0 to 16%. If the moisture content is 18% or more, the microfiber cellulose composite resin may become colored. In particular, when the modification rate of the carbamate group is set to 1 mmol / g or more, coloring may not be reduced.

[0137] In order to reduce coloring, for example, a method can be adopted in which hemicellulose, which is one of the components of cellulose (a coloring substance), is depolymerized to make it water-soluble, and the coloring substance is removed in a washing process of the carbamate cellulose. If the coloring substance remains in the microfiber cellulose, the resin and the coloring substance will come into contact during the kneading process, causing noticeable coloring.

[0138] The moisture content was calculated using the following formula by holding a sample at 105°C for 6 hours or more in a constant temperature dryer and measuring the mass after drying at the point where no change in mass was observed. Moisture content (%) = [(mass before drying - mass after drying) ÷ mass before drying] × 100

[0139] (Kneading process) The microfiber cellulose-containing material (resin reinforcing material) obtained as described above is kneaded with resin to obtain a microfiber cellulose composite resin. This kneading can be performed, for example, by mixing the pellet-shaped resin with the reinforcing material, or by melting the resin first and adding the reinforcing material to the melt. Note that acid-modified resins, dispersants, etc. can also be added at this stage.

[0140] In the kneading step, for example, one or more types of kneaders can be selected from a single-shaft kneader, a multi-shaft kneader having two or more shafts, a mixing roll, a kneader, a roll mill, a Banbury mixer, a screw press, a disperser, etc. Among these, it is preferable to use a multi-shaft kneader having two or more shafts. Two or more multi-shaft kneaders having two or more shafts may be used in parallel or in series.

[0141] The temperature in the kneading step is preferably equal to or higher than the glass transition point of the resin, and although it differs depending on the type of resin, it is preferably 80 to 350°C, more preferably 90 to 300°C, and particularly preferably 100 to 280°C.

[0142] As the resin, it is preferable to use at least one of a thermoplastic resin and a thermosetting resin.

[0143] As the thermoplastic resin, for example, one or more selected from polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polyacrylic resins such as polystyrene, methacrylate and acrylate, polyamide resins, polycarbonate resins, polyacetal resins, etc. can be used.

[0144] However, it is preferable to use at least one of polyolefin and polyester resin. As the polyolefin, it is preferable to use polypropylene. As the polyester resin, examples of the aliphatic polyester resin include polylactic acid and polycaprolactone, and examples of the aromatic polyester resin include polyethylene terephthalate, but it is preferable to use a biodegradable polyester resin (also simply called "biodegradable resin").

[0145] As the biodegradable resin, for example, one or more types may be selected from hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, dibasic acid polyesters, and the like and used.

[0146] As the hydroxycarboxylic acid-based aliphatic polyester, for example, one or more of homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, glucose acid, 3-hydroxybutyric acid, and copolymers using at least one of these hydroxycarboxylic acids can be selected and used. However, it is preferable to use polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids other than lactic acid, polycaprolactone, and copolymers of at least one of the above hydroxycarboxylic acids and caprolactone, and it is particularly preferable to use polylactic acid. As this lactic acid, for example, L-lactic acid, D-lactic acid, and the like can be used, and these lactic acids may be used alone or two or more of them may be selected and used.

[0147] As the caprolactone-based aliphatic polyester, for example, one or more types may be selected from homopolymers of polycaprolactone and copolymers of polycaprolactone or the like with the above-mentioned hydroxycarboxylic acids and the like.

[0148] As the dibasic acid polyester, for example, one or more types may be selected from polybutylene succinate, polyethylene succinate, polybutylene adipate, and the like and used.

[0149] The biodegradable resin may be used alone or in combination of two or more kinds.

[0150] Examples of the thermosetting resin that can be used include phenol resins, urea resins, melamine resins, furan resins, unsaturated polyesters, diallyl phthalate resins, vinyl ester resins, epoxy resins, urethane resins, silicone resins, thermosetting polyimide resins, etc. These resins can be used alone or in combination of two or more.

[0151] The resin may contain an inorganic filler. Examples of the inorganic filler include simple substances of metal elements in Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon, as well as oxides, hydroxides, carbonates, sulfates, silicates, and sulfites, and various clay minerals composed of these compounds.

[0152] Specific examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, silica, heavy calcium carbonate, light calcium carbonate, aluminum borate, alumina, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay wollastonite, glass beads, glass powder, silica sand, silica stone, quartz powder, diatomaceous earth, white carbon, glass fiber, etc. A plurality of these inorganic fillers may be contained. Also, it may be one contained in waste paper pulp.

[0153] The blending ratio of microfiber cellulose to resin is preferably microfiber cellulose:resin=1-99% by mass:99-1% by mass, more preferably 5-95% by mass:95-5% by mass, and even more preferably 10-90% by mass:90-10% by mass. If the ratio of microfiber cellulose is lower than the above blending ratio range, the amount of microfiber cellulose is small, so the strength of the three-dimensional network formed by the microfiber cellulose connecting the resins in the composite resin is weak, and the reinforcing effect of the resin is poor. On the other hand, if the ratio of microfiber cellulose is higher than the above blending ratio range, even if the microfiber cellulose has a reinforcing effect of the resin, the strength inherent to the resin is not exhibited, and the composite resin may not have the desired strength.

[0154] The content ratio of the microfiber cellulose and the resin contained in the finally obtained composite resin is usually the same as the above-mentioned blending ratio of the microfiber cellulose and the resin.

[0155] Solubility parameters (cal / cm) of microfiber cellulose and resin 3 The difference between the SP values ​​is expressed as follows: SP value difference = SPMFC value - SPPOL value. The SP value difference is preferably 10 to 0.1, more preferably 8 to 0.5, and particularly preferably 5 to 1. If the SP value difference exceeds 10, the dispersibility of the microfibrous cellulose in the resin is insufficient, and it is possible that the reinforcing effect cannot be obtained. On the other hand, if the SP value difference is less than 0.1, the microfibrous cellulose dissolves in the resin, does not function as a filler, and the reinforcing effect cannot be obtained. It can be said that the smaller the difference between the SPPOL value of the resin (solvent) and the SPMFC value of the microfibrous cellulose (solute), the greater the reinforcing effect.

[0156] The solubility parameter (cal / cm 3 )1 / 2 (SP value) is a measure of the intermolecular force acting between a solvent and a solute, and the closer the SP values ​​of the solvent and solute are, the greater the solubility.

[0157] (molding process) The mixture of the microfiber cellulose-containing material and the resin can be molded into a desired shape after being kneaded again as necessary. The size, thickness, shape, etc. of the molded product are not particularly limited, and can be, for example, a sheet, pellet, powder, fiber, etc.

[0158] The temperature during the molding step should be equal to or higher than the glass transition point of the resin, and differs depending on the type of resin. For example, a temperature of 90 to 260° C., preferably 100 to 240° C., is preferable because sufficient kneading can be achieved.

[0159] The kneaded product can be molded by, for example, mold molding, injection molding, extrusion molding, blow molding, foam molding, etc. The kneaded product can also be spun into fibers and mixed with plant materials or the like to form a mat or board. The fibers can be mixed by, for example, a method of simultaneous deposition by air laying. As a device for molding the kneaded product, one or more types can be selected from, for example, an injection molding machine, a blow molding machine, a blow molding machine, a compression molding machine, an extrusion molding machine, a vacuum molding machine, a pressure molding machine, etc.

[0160] Examples of plant materials that can be mixed include fibers derived from plant materials obtained from various plants such as kenaf, jute, Manila hemp, sisal, gampi, mitsumata, paper mulberry, banana, pineapple, coconut, corn, sugarcane, bagasse, palm, papyrus, reed, esparto, sabai grass, wheat, rice, bamboo, various coniferous trees (such as cedar and cypress), broad-leaved trees, and cotton.

[0161] The above molding can be carried out following kneading, or the kneaded mixture can be cooled once and then chipped using a crusher or the like, and the chips can be fed into a molding machine such as an extrusion molding machine or an injection molding machine. Of course, molding is not an essential requirement of the present invention. EXAMPLES

[0162] Next, an example of the present invention will be described. As a cellulose raw material, a sheet-shaped softwood kraft pulp (NBKP) having a moisture content of 10% or less was prepared. This cellulose raw material had a basis weight of 50 to 800 g / m 2 The cellulose raw material was impregnated with a 20% by mass aqueous solution of urea and betaine to form a mixture, which was then left to dry at 105°C for 6 hours. The amounts of the cellulose raw material (softwood kraft pulp), 20% by mass aqueous solution of urea, and betaine added (mass converted into solid content) are as shown in [Table 1]. The mixture was then reacted at the reaction temperature and reaction time shown in [Table 1] to obtain carbamate cellulose. The obtained carbamate cellulose was diluted with distilled water, stirred, and dehydrated, and this washing process was repeated twice. The carbamate cellulose after the washing process was beaten using a beater until the fine ratio (the ratio of fibers of 0.2 mm or less as measured by fiber length distribution measurement using a fiber analyzer "FS5") was 77% or more, to obtain carbamate microfiber cellulose. The crystallinity of the cellulose raw material (NBKP), the crystallinity of the carbamate cellulose, and the modification ratio (carbamation ratio) of the microfiber cellulose were measured. The results obtained are shown in Table 1.

[0163] [Table 1]

[0164] The carbamate conversion rate was evaluated according to the following criteria. ◎: The carbamate conversion rate is 1.80 mmol / g or more. ◯: The carbamate conversion rate is greater than 1.25 mmol / g and less than 1.80 mmol / g. ×: The carbamate conversion rate is 1.25 mmol / g or less.

[0165] In addition, the crystallinity of Test Example 1 was 85% before carbamate conversion, and 84% for carbamate cellulose (before beating), showing that the crystallinity did not change significantly before and after carbamate conversion. The crystallinity of Test Example 4 was also 85% before carbamate conversion, and 84% for carbamate cellulose (before beating). [Industrial Applicability]

[0166] INDUSTRIAL APPLICABILITY The present invention can be used as a method for producing microfibrous cellulose, a method for producing microfibrous cellulose composite resin, and microfibrous cellulose.

Claims

1. a modification step of modifying a cellulose raw material to obtain carbamate cellulose; A defibration step of defibrating the carbamate cellulose to obtain microfibrous cellulose, The modification step is carried out by adding urea or a derivative thereof and betaine to a cellulose raw material and heating the mixture to 100 to 300° C. The modification rate of the carbamate group in the microfibrous cellulose is 0.5 to 3.0 mmol / g. A method for producing microfibrous cellulose.

2. The cellulose raw material is a sheet-like pulp. The method for producing the microfibrous cellulose according to claim 1 .

3. Add urea or its derivative and betaine in a mass ratio of 1:99 to 99:1; The method for producing the microfibrous cellulose according to claim 1 or 2.

4. The microfiber cellulose has an average fiber width of 0.1 to 15 μm. The method for producing the microfibrous cellulose according to any one of claims 1 to 3.

5. The denaturation step is carried out by heating for 1 second or more and 2 hours or less. The method for producing the microfibrous cellulose according to any one of claims 1 to 4.

6. A kneading step of kneading the microfiber cellulose obtained by the production method according to any one of claims 1 to 5 with a resin to obtain a cellulose composite resin, A method for producing a cellulose composite resin comprising the steps of:

7. a modification step of modifying a cellulose raw material to obtain carbamate cellulose; The method includes a defibration step of defibrating the carbamate cellulose, The modification step is carried out by adding urea or a derivative thereof and betaine to a cellulose raw material and heating the mixture to 100 to 300° C. The fiber is obtained by the defibration step, has a crystallinity of 50 to 95%, and has a modification rate of carbamate groups of 0.5 to 3.0 mmol / g. Microfiber cellulose.

Citation Information

Patent Citations

  • Modified cellulose fiber-containing resin composition, molding material and molded body

    JP2016216605A

  • Method for producing chemically modified cellulose fiber

    JP2019070084A

  • Sulfonated pulp fibers, derivative pulp, sulfonated fine cellulose fibers, method for making sulfonated fine cellulose fibers, and method for making sulfonated pulp fibers

    JP2021025049A

  • Fibrous cellulose composite resin, and manufacturing method thereof

    JP2021031662A

  • Sulfated fibrous cellulose, composition, sheet, and sulfated fibrous cellulose production method

    JP2021042319A